Single-mom adventures with autism: living through my son's surgery - Cohen, Phoebe (Research and Humanities in Medical Education, 2019)
This is a story about my autistic son's surgery. Autistic patients are very common in the medical field but they aren't very well represented in graphic novels or medical literature. This is a simple story about my 6-year-old son's minor dental surgery and the various steps that medical professionals must take to accommodate autistic patients. Through this graphic story I try to show the challenges that parents and doctors must deal with on a daily basis when it comes to the health of autistic children.